2020
DOI: 10.3390/biology9030044
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection Induces High Expression of Prolactin and Prolactin Receptors in Ovarian Cancer

Abstract: One of the potential biomarkers for ovarian cancer patients is high serum level of prolactin (PRL), which is a growth factor that may promote tumor cell growth. The prolactin receptor (PRLR) and human cytomegalovirus (HCMV) proteins are frequently detected in ovarian tumor tissue specimens, but the potential impact of HCMV infection on the PRL system have so far not been investigated. In this study, HCMV’s effects on PRL and PRLR expression were assessed in infected ovarian cancer cells (SKOV3) by PCR and West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Studies have demonstrated that prolactin (PRL) has more than 300 other functions in addition to regulating the development of breast and lactation (1)(2)(3)(4)(5). Among them, the regulatory roles of PRL in metabolism has been a focus of research in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that prolactin (PRL) has more than 300 other functions in addition to regulating the development of breast and lactation (1)(2)(3)(4)(5). Among them, the regulatory roles of PRL in metabolism has been a focus of research in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Their study proved the role of HCMV as an oncomodulator rather than involving in direct transformation. Rahbar et al recently found that prolactin(PRL) and prolactin(PRLR) receptor were induced to high levels in HCMV-infected ovarian cancer cells and PRLR expression was extensively detected in HCMV-infected ovarian tissue specimens [29]. Highly induced PRL and PRLR by HCMV infection may be of relevance for the oncomodulatory role of HCMV in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Their study proved the role of HCMV as an oncomodulator rather than involving in direct transformation. Rahbar et al [29] recently found that prolactin(PRL) and prolactin(PRLR) receptor were induced to high levels in HCMV-infected ovarian cancer cells and PRLR expression was extensively detected in HCMV-infected ovarian tissue specimens. Highly induced PRL and PRLR by HCMV infection may be of relevance for the oncomodulatory role of HCMV in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%